IMPLEMENTATION OF THE GYMNASTICS CURRICULUM IN THE FIRST THREE-YEAR CYCLE OF THE PRIMARY SCHOOL IN SLOVENIA - Marjeta Kovač; Vedrana Sember; Maja Pajek (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
Throughout the world, gymnastics is an essential part of physical education (PE) curricula, especially in the first years of schooling. In this period, PE is taught by the general teachers (GTs) with low levels of experience about how to teach gymnastics. Our study aimed to find out how GTs complied with the prescribed gymnastics curriculum contents. The sample included 90 GTs from 21 primary schools from Ljubljana, the capital of Slovenia. A self-administered questionnaire was designed to examine the opinions of GTs about some factors of importance and implementation of gymnastics contents on a five-level Likert scale. A one-way ANOVA, Tukey post hoc test, and Mann-Whitney U test were used in the data processing. GTs allocated more time to those contents of the PE curriculum that rank higher regarding the importance of child development and are easier to teach. They spent only 16.93 lessons on gymnastics per academic year, ranked gymnastics at fourth place (out of 7) regarding its importance for children's development, and gymnastics seemed to be the most challenging content to teach. Within gymnastic content, the least implemented elements were those mentioned as the most difficult to learn for children (acrobatics, hang and support, and vaults). GTs believed that teaching methods (4.29) were less important for successful gymnastics performance than children's motor efficiency (4.73) and self-activity (4.57). The outcomes of this study may aid in the future updating of GT education study programmes and designing a creative system of continuous professional development.